Partial remission with cyclosporine A in a patient with nephrotic syndrome due to NPHS2 mutation - Malina, Michal; Cinek, Ondrej; Janda, Jan; Seeman, Tomas (Pediatric nephrology (Berlin, Germany), 2009)
Autosomal recessive steroid-resistant nephrotic syndrome (NS) is a rare, genetically determined nephropathy caused mainly by a mutation in the NPHS2 gene. This type of NS is usually resistant to other immunosuppressive therapy as well, but a few cases of cyclosporine A-induced partial remission of inherited NS have been reported. We present a boy that developed NS at the age of 18 months. There was no decrease of proteinuria on standard prednisolone therapy, and a diagnosis of steroid-resistant NS was established. However, the proteinuria decreased significantly following the initiation of cyclosporine A therapy (from 1280 to 380 mg/m(2) per day) without any negative effects on renal function (stable glomerular filtration rate 130-150 ml/min per 1.73 m(2)). The molecular genetic test revealed a homozygous R138Q mutation in the NPHS2 gene. Our case demonstrates that cyclosporine A can induce partial remission in patients with genetic forms of NS without influencing the glomerular filtration rate. However, its long-term effect and safety in children with hereditary forms of nephrotic syndrome have yet to be investigated.
Keywords: Nephrotic Syndrome; lidé; mužské pohlaví; Infant; Immunosuppressive Agents; cyklosporin; Male; Remission Induction; kojenec; Transcription Factors; transkripční faktory; imunosupresiva; indukce remise; nefrotický syndrom; Cyclosporine; Humans